The Work of Reconstruction: From Slave to Wage Laborer in South Carolina, 1860-1870 - O'Brien, John T. (Labour / Le Travail, 1998)
The article reviews the book, "The Work of Reconstruction: From Slave to Wage Laborer in South Carolina, 1860-1870," by Julie Saville.